2007
DOI: 10.1177/0363546507308362
|View full text |Cite
|
Sign up to set email alerts
|

Knee Valgus during Drop Jumps in National Collegiate Athletic Association Division I Female Athletes

Abstract: A medial post may be a potential means to decrease risk of anterior cruciate ligament injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 39 publications
4
53
3
Order By: Relevance
“…7 Rearfoot eversion (a component of foot pronation) has been hypothesized to contribute to tibial abduction and in turn knee frontal plane angle. 1,13 This premise is supported by the work of Williams et al, 28 who found that frontal plane knee position changed in response to an alteration in frontal plane ankle position during running. Despite the fact that ankle dorsiflexion was measured in a non-weight-bearing position in the current study, a relationship between ankle range of motion and frontal plane knee excursion was found.…”
Section: Intratester Reliability For Measurementsmentioning
confidence: 80%
“…7 Rearfoot eversion (a component of foot pronation) has been hypothesized to contribute to tibial abduction and in turn knee frontal plane angle. 1,13 This premise is supported by the work of Williams et al, 28 who found that frontal plane knee position changed in response to an alteration in frontal plane ankle position during running. Despite the fact that ankle dorsiflexion was measured in a non-weight-bearing position in the current study, a relationship between ankle range of motion and frontal plane knee excursion was found.…”
Section: Intratester Reliability For Measurementsmentioning
confidence: 80%
“…13,42,58,68 In a 1-legged stance, ipsilateral trunk lean would move the center of body mass toward the stance leg, with the effect of reducing the external hip-adduction moment and therefore the demands on the hip-abductor muscle group. If subjects with weak hip abductors used this mechanism of compensation, it may reduce the effects of weak abductors on kinematics below the hip.…”
Section: Discussionmentioning
confidence: 99%
“…We instruct the female athlete to control the knees via the hip/pelvis 68,86,132 and foot position. 86 Furthermore, we emphasize strength training of the hip abductors, extensors, and external rotators. We take special consideration to eccentrically train these muscle groups to help control excessive adduction and internal rotation of the femur during WB activities.…”
Section: 79mentioning
confidence: 99%